2004
DOI: 10.1038/ng1321
|View full text |Cite
|
Sign up to set email alerts
|

Oculofaciocardiodental and Lenz microphthalmia syndromes result from distinct classes of mutations in BCOR

Abstract: Lenz microphthalmia is inherited in an X-linked recessive pattern and comprises microphthalmia, mental retardation, and skeletal and other anomalies. Two loci associated with this syndrome, MAA (microphthalmia with associated anomalies) and MAA2, are situated respectively at Xq27-q28 (refs. 1,2) and Xp11.4-p21.2 (ref. 3). We identified a substitution, nt 254C→T; P85L, in BCOR (encoding BCL-6-interacting corepressor, BCOR 4 ) in affected males from the family with Lenz syndrome previously used to identify the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
304
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 282 publications
(313 citation statements)
references
References 26 publications
8
304
0
1
Order By: Relevance
“…Like in frog (Hilton et al, 2007;Sakano et al, 2010), BCoR mutations randomize LR asymmetry in human embryos (Ng et al, 2004;Hilton et al, 2007), but this does not occur in mouse (Ye et al, 1997;Yoshida et al, 1999). The loss of brain asymmetry observed in mouse mutants with ciliary dyskinesia (Kawakami et al, 2008) is not observed in human patients (Kennedy et al, 1999;Tanaka et al, 1999;McManus et al, 2004;Afzelius and Stenram, 2006).…”
Section: The Mouse As a Model For Mammalian Asymmetrymentioning
confidence: 93%
“…Like in frog (Hilton et al, 2007;Sakano et al, 2010), BCoR mutations randomize LR asymmetry in human embryos (Ng et al, 2004;Hilton et al, 2007), but this does not occur in mouse (Ye et al, 1997;Yoshida et al, 1999). The loss of brain asymmetry observed in mouse mutants with ciliary dyskinesia (Kawakami et al, 2008) is not observed in human patients (Kennedy et al, 1999;Tanaka et al, 1999;McManus et al, 2004;Afzelius and Stenram, 2006).…”
Section: The Mouse As a Model For Mammalian Asymmetrymentioning
confidence: 93%
“…In addition to its role in B-cells, BCOR aids in the control of gene expression in multiple tissues and organ systems during development and into adulthood as mutations in human BCOR result in X-linked Oculofaciocardiodental syndrome (OFCD) (Ng et al, 2004). OFCD is the primary subtype of OMIM #300166 microphthalmia, syndromic 2 (MCOPS2) and is characterized by ocular, dental, cardiac and digital anomalies in heterozygous females (Ng et al, 2004;Schulze et al, 1999).…”
Section: )mentioning
confidence: 99%
“…OFCD is the primary subtype of OMIM #300166 microphthalmia, syndromic 2 (MCOPS2) and is characterized by ocular, dental, cardiac and digital anomalies in heterozygous females (Ng et al, 2004;Schulze et al, 1999). Males with OFCD do not survive due to presumed embryonic lethality (Ng et al, 2004).…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations